Caracterización y determinación del potencial Aterogénico de quesos producidos en Costa Rica - Chavarría Sánchez, Jéssica; Herrera Ramírez, Carlos; Lutz, Giselle (Revista de Ciencia y Tecnología, 2009)
Cardiovascular diseases have been one of the main causes of mortality during the past years in Costa Rica. Many risk factors associated to these disorders include the intake of high-fat diets, being cheese an example of such a dietary component. Thus, the fatty-acid characterization of different cheeses was needed, in order to obtain a more ample scope of this public health issue. Cheeses derived from both bovine and caprine milks were included in this study. The Laboratorio Costarricense de Metrología of the Ministry of Economy, Industry and Commerce carried out the sampling needed for this work. The chemical parameters determined in the samples studied were: fatty acid composition (by GC and NMR techniques), saponification and iodine numbers, average triacylglycerol molecular weight, polyunsaturated fatty acids / saturated fatty acids ratio, atherogenic index and number of allylic hydrogens. The experimental values of water and lipid content found were compared with the data in the nutritional-fact labels, designed according to existing national and international food regulations.